Pendidikan Karakter Dalam Teks Cerita Anusasana Parwa - Budayasa, I Made Rai (Jayapangus Press, 2022)
The Anusasana Parwa story is the 13th part of the Asta Dasa Parwa or 18 Parwa in the Mahabharata story, which tells the story of Yudisthira's coronation as king of Hastina replacing his uncle Drestarastra. In this parwa, it is described how the great king of the Kuru people was able to reconcile himself. The awareness that grew within Yudisthira was obtained after receiving teachings from his grandfather Bhisma. This Parva explains in detail the rules regarding Dharma. So in the Mahabharata story there are many character education values ​​which can be used as guidelines for behavior. The issues that will be discussed include: (1) The Anusasana Parwa story (2) The value of character education contained in the Anusasana Parwa story; The aim of this research is to preserve literary works as a form of language art that should be maintained, developed and interpreted. Works can expand Balinese cultural treasures. Apart from that, this research provides information about the existence of Hindu literary works which are full of the teachings of sraddha bhakti, morals and ethics. The theories applied to analyze the problem formulation in this work are: Teeuw's Structuralism theory, Koentjaraningrat's Value theory; Data collection methods are literature study, interviews, documentation which focuses on reviewing written sources in the library; The data collected and obtained will be analyzed using qualitative descriptive analysis methods, with reduction steps, data presentation and drawing conclusions; The results obtained from the research show (1) Anusasana Parwa story text. (2) In the Anusasana Parwa story text there are character education values ​​that shape students' characters, namely religious character, curiosity character, social care character, tolerance character, and love of reading character; So it can be concluded that there is character education in the story of Anusasana Parwa.